Electrophysiology of Error Processing : Motivational and Affective Correlates - Leland, David S.; Lockington, Ronnie J.; Loew, Sarah T.; Moe, Simon M.; Yonker, A'Lea M.; Becker, Samuel J.; Brandt, Lucas J.; Rolefson, Kelsey A. (My University, 2017)
Clinical Perfectionism is the overdependence on self‐evaluation for the determined pursuit of personally demanding, self‐imposed, standards in at least one highly-salient domain, despite adverse consequences (Shafran et al., 2002). We hypothesize that either or both the ERN and Pe will be positively correlated with clinical perfectionism. We also aim to replicate classic ERN and Pe findings associated with error processing, anxiety, depression, and fear of failure.
Color poster with text, charts, and graphs.
Keywords: Electrophysiology; Error-related negativity (ERN); Psychology; Perfectionism; Posters